IMAGERY IN POERTRY COLLECTION TUHAN, KITA BEGITU DEKAT THE WORK OF ABDUL HADI W.M. - Khoridah, Destiara Khoridah; Rumadi, Hadi Rumadi; ', Syafrial (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT: This study is titled imagery in poetry collection Tuhan Kita Begitu Dekat the work of Abdul Hadi W.M. This study aimed to describe the visual imagery, to describe auditory imagery, to describe olfactory  imagery, to describe tactile imagery, to describe subjective imagery, to describe gustatory imagery, and to describe kinesthetic imagery, the method with qualitative approach. The research data are from lines in poems that contained visual, auditory, olfactory, tactile, subjective, gustatory and kinesthetic imagery. The result of the study is that there are 82 data found from 77 poems with the total number of data are 103 poems. From those data, there are visual imagery as many as 22 of 19 poems. 36 auditorory imagery data from 35 poems, 4 olfactory imagery data from 4 foems, 3 tactile imagery data from 3 poems, 4 subjective imagery data from 4 poems, 2 gustatory imagery data from 2 poems, and 11 kinesthetic imagery data from 10 poems. The dominant imagery is the visual and auditory imagery. Those imagery are capable of moving the reader’s imagination into unconsciousness area that transcends the ordinary consciousness. The feelings that are suggested in the poems are happiness, sadness and even heartache. Keywords : Imagery in poerty